Pitfalls in Labelled Leukocyte Scanning - H Hodgson; M Roddie (Canadian Journal of Gastroenterology)
Radiolabelled leukocyte scanning is a valuable tool in the diagnosis and management of inflammatory bowel disease (IBO). As well as determining the presence or absence of disease and its complications, the degree of inflammation may be quantified either visually or numerically following four day fecal collection. The authors discuss the labelling techniques currently in use and the appearance of IBO using both 111Indium and 99mTechnetium as the labelling isotope. The advantages and disadvantages of each technique are compared. Certain diagnostic pitfalls and causes of false-positive results including radiation enteritis, nonsteroidal anti-inflammatory drug ingestion and intra- and extra-abdominal sepsis are discussed in full, and it is shown that in most cases good labelling technique, careful imaging and awareness of alternative mechanisms for leukocyte appearance in the gastrointestinal tract will ensure correct interpretation of these scans.